Pengaruh Kualitas Informasi Dan Sistem Layanan Terhadap Minat Beli Ulang Pengguna E-Commerce Situs Lazada.Com Pada Masyarakat Desa Limau Manis Kecamatan Tanjung Morawa Kab. Deli Serdang - Evi Syahputri; Indra Utama (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
The purpose of this research is to find out and see the influence of the quality of information, systems and services on the interest of repurchasing e-commerce users of Lazada.com site in the community of Limau Manis Village, Tanjung Morawa District, Kab. Deli Serdang Research design is a framework or details of work procedures that will be carried out at the time of research, so it is hoped that it can provide an overview and direction in which to carry out the research, as well as provide an illustration if the research has been completed or the research is completed. The design of this study uses a quantitative approach, aiming to determine the relationship between two or more variables. The t-value for the Information Quality variable (X1) is 5.090 when compared to the t-table value of 1.666. Then the t-count obtained is greater than the t-table value or 5.090 1.666, the t-count value for the Service System variable (X2) is 7,454 when compared to the t-table value of 1,666, it is concluded that the independent variables X1, and X2 simultaneously have a positive and significant to the dependent variable Y. Limau Manis Village must pay attention to the quality of information and service systems. It is hoped that Limau Manis Village can maintain and improve the quality of information and service systems, because from the above discussion the quality of information and service systems has a significant influence on buying interest. For further researchers, if you want to do research related to the quality of information and service systems, it is expected to add other factors that can affect the intention to repurchase e-commerce users on the Lazada.com site.Keywords: Information Quality, Service System and Purchase Interest